2011
DOI: 10.1134/s1995078011060127
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbiturils as containers for medicinal compounds

Abstract: The drug efficacy problem related to the stability of medicinal preparations and to the specificity of their action is now among the most important in pharmacology and medicine. One way to solve this prob lem is to create structures with the ability to encapsulate a therapeutic agent in order to release it over a given time at a particular site. Cucurbiturils are an example of such "host molecules." Encapsulation will allow us to increase the solubility of compounds, control the release of an agent and its cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…To some extent, the solubility of these members might be enhanced by utilizing cations or positively charged guest molecules [87,88]. Additionally, solubility issue might be surpassed by synthesizing substituted CB[n]s with units that could enhance the solubility of CB[n]s in common solvents and also provides a handle that is suitable for further functionalization [87] [98][99][100][101]. The guest encapsulation is facilitated by ion-dipole interactions and through (non-)classical hydrophobic effects [102,103].…”
Section: Synthesis and Properties Of Cucurbit[n]urilsmentioning
confidence: 99%
“…To some extent, the solubility of these members might be enhanced by utilizing cations or positively charged guest molecules [87,88]. Additionally, solubility issue might be surpassed by synthesizing substituted CB[n]s with units that could enhance the solubility of CB[n]s in common solvents and also provides a handle that is suitable for further functionalization [87] [98][99][100][101]. The guest encapsulation is facilitated by ion-dipole interactions and through (non-)classical hydrophobic effects [102,103].…”
Section: Synthesis and Properties Of Cucurbit[n]urilsmentioning
confidence: 99%
“…Cucurbit [7]uril hydrate (Sigma-Aldrich, powder containing 80% Q7 and 20% water), gemcitabine hydrochloride (Sigma-Aldrich, powder, C 98%), hydrochloric acid fixonal (POCh, 1 M), sodium hydroxide (POCh, C 99.8%), sodium chloride (Sigma-Aldrich, C 99.5%) were purchased from commercial sources. Water (for ITC and pHmetric titration) was distilled three times and degassed .…”
Section: Methodsmentioning
confidence: 99%
“…Many research centers have carried out studies on the use of cucurbiturils as transporters of toxic medicines [7], including oncological drugs [8][9][10][11]. Cucurbiturils (CB, Q) are a relatively new group of macrocyclic compounds, whose structures contain a repeatedly duplicated motif of glycoluril [12].…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Recently,C Bns have been explored as drug carriers that improve chemical stabilitya nd solubility of their drug payload. [26,30,31] Further,CB7 has shown utility for controlled release of drugs in cancerous cells. [32] Cao et al reported synthesis of a directly biotinylated CB7 (btCB7, Figure 1a)a sacarrier for anticancer drugs to murine lymphocytic leukemia (L1210FR) cancer cells, which overexpress biotin receptors.…”
mentioning
confidence: 99%